Clinical and pathological assessment of the calystegines in Ipomoea carnea in a goat model - Daniel Cook; Bryan L. Stegelmeier; Dale R. Gardner; Franklin Riet-Correa; Clinton A. Stonecipher; Kevin D. Welch (Toxicon, 2026)

Pharmaceutical pollution in a wastewater-impacted coastal ecosystem - Raiko Rafeeq; Erinn K. Richmond; Wei Wen Wong; Daniel Cerveny; Tomas Brodin; Minna Saaristo; Michael R. Grace; Perran Cook; Bob B.M. Wong (Environmental Pollution, 2026)

The use of pumping for hydraulic characterisation of dykes - Vair J. Pointon; Ilka Wallis; Daniel Partington; Paul Hedley; Peter G. Cook (Hydrogeology Journal, 2026)
Faults and dykes can control groundwater flow, acting as barriers, conduits, or composite conduit–barrier systems. This study investigates dyke hydraulic behaviour using numerical modelling of field-scale pumping tests at two sites in Western Australia, supported by a uniquely detailed hydrogeological dataset. At each site, pumping tests were conducted across dykes that impeded groundwater flow, as evidenced by asymmetric drawdown cones and delayed responses in observation wells situated across the dyke from the pumping well. High-resolution three-dimensional geological frameworks were developed, and transient groundwater flow models were calibrated using automated inversion with and without spatially variable parameterisation (pilot points) to represent heterogeneity. In all calibrated models, the horizontal hydraulic conductivity ( K h ) of dykes was estimated to be one to eight orders of magnitude lower than that of the surrounding formations. Representation of dykes in the model produced the largest improvement in model fit at both sites, reducing the parameterisation objective function by one to two orders of magnitude relative to model parameterisations without dykes. Further improvements in model fit were achieved by introducing heterogeneity into formations, dykes or both. Although including formation heterogeneity reduced posterior uncertainty in dyke K h estimates, posterior variance patterns revealed that, in some locations, calibration preferentially adjusted K h in formations adjacent to dykes rather than within the dykes. Dyke K h was tightly constrained in areas with available field data and observable drawdown. These findings demonstrate the importance of representing structural features when interpreting pumping-test responses in structurally complex groundwater systems.

Analysis of second-generation epigenetic clocks reveals further associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Vincent Doré; Pierrick Bourgeat; Rosita Shishegar; James D. Doecke; Paul Maruff; Christopher C. Rowe; Victor L. Villemagne; Michael Weiner; Paul Aisen; Ronald Petersen; et al. (GeroScience, 2026)

A Jelly-Eating Hitchhiker in the Mediterranean: Molecular Identification of Brachyscelus rapacoides Stephensen 1925 (Amphipoda: Brachyscelidae) in Greece - Konstantinos Kalaentzis; Paraskevi Louizidou; Gerasimos Kondylatos; Elisavet Kaitetzidou; Lyndall Pereira da Conceicoa; Mara Lawniczak; Alex Makunin; Jack Monaghan; Paul Heath; Craig Corton; James Watts; Michelle Smith; et al. (Thalassas: An International Journal of Marine Sciences, 2026)
The hyperiid amphipod Brachyscelus rapacoides is a warm-water species associated with gelatinous zooplankton. In the Mediterranean it has been reported in association with Rhopilema nomadica in both Israel and Turkey. Here, we document the first record of B. rapacoides in Greek waters, representing the first confirmed record for Europe, based on both morphological examination and DNA barcoding of the mitochondrial COI gene. Specimens were collected from the umbrella of infested R. nomadica from two localities in the southeastern Aegean Sea. Diagnostic morphological characters, particularly the dentition of gnathopods 1–2 and male antennal morphology, agree with published redescriptions of the species. Phylogenetic analyses placed the studied specimens within B. rapacoides , clearly separated from congeners. This finding extends the known distribution of the species westwards in the Mediterranean and further supports its close ecological association with R. nomadica . The record highlights the role of gelatinous hosts in facilitating dispersal of symbiotic hyperiids and underscores the importance of integrating molecular tools and citizen science observations for early detection of overlooked pelagic associates.

A systems modelling approach to predict biological responses to extreme heat - Daniel W.A. Noble; Margaret M. Mayfield; Ary A. Hoffmann; Zhong-Hua Chen; Steven J. Lade; Xuemei Bai; Danielle A. Way; Belinda E. Medlyn; Owen K. Atkin; Adrienne B. Nicotra; James M. Cook; Brajesh K. Singh; et al. (Trends in Ecology & Evolution, 2026)

Implications of sulphide toxicity for seed-based seagrass restoration - Laney Callahan; Rhys A. Coleman; Lawrence Webb; Perran LM. Cook; Daniel Ierodiaconou; Craig DH. Sherman (Marine Environmental Research, 2026)

SNAPSHOT USA 2024: Year 6 of the Coordinated National Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Daniel J. Herrera; Camilla Price; Phuong‐Thao Nguyen‐Nu; Katrina Adamczyk; Peter D. Alexander; David Allen; Jesse M. Alston; Diego F. Alvarado‐Serrano; et al. (Global Ecology and Biogeography, 2026)
Motivation SNAPSHOT USA is an annual, multi‐contributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2024 contains 377,427 records of camera trap image sequence data and 3127 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in 49 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1 August and 19 December in 2024. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2024 comprises two .csv files. The original data can be found within the SNAPSHOT USA 2024 project on the Wildlife Insights platform.

Collaborative evaluation of in silico predictions for high throughput toxicokinetics - John F. Wambaugh; Nisha S. Sipes; Gilberto Padilla Mercado; Jon A. Arnot; Linda Bertato; Trevor N. Brown; Nicola Chirico; Christopher Cook; Daniel E. Dawson; Sarah E. Davidson-Fritz; Stephen S. Ferguson; Michael-Rock Goldsmith; et al. (Toxicology in Vitro, 2026)

The Toxicology Investigators Consortium 2024 Annual Report - Kim Aldy; Shao Li; Mari Costantini; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; Michael Abesamis; Faiz Ahmed; Salman Ahsan; Peter Akpunonu; Adam Algren; et al. (Journal of Medical Toxicology, 2026)

Corrigendum to Toward a near-lossless image compression strategy for the NASA/USGS Landsat Next mission Remote Sensing of Environment Volume 329, 1 November 2025, 114929 - Rehman S. Eon; Craig De Groot; Jeffrey A. Pedelty; Aaron Gerace; Matthew Montanaro; Richard K. Covington; Amy S. DeLisa; Wen-Ting Hsieh; Joy M. Henegar-leon; Douglas J. Daniels; Christopher Engebretson; Christopher J. Crawford; et al. (Remote Sensing of Environment, 2025)

Bridging extreme climate risks, financial precarity, and adaptation gaps: Advancing inclusive adaptation in rainfed agricultural systems - Van Touch; Ariane Utomo; De Li Liu; Nicholas Harrigan; Le-Anne Bannan; Panhaleak Chay; Caitlin Finlayson; Kirt Hainzer; Andrew McGregor; Katharine McKinnon; Lita Mom; Sophanara Phan; et al. (Global Environmental Change, 2025)

Reshaping agricultural production systems: Trade-offs and implications for sustainable intensification and environment management - Van Touch; Ariane Utomo; Nicholas Harrigan; Caitlin Finlayson; Andrew McGregor; Katharine McKinnon; Thong Anh Tran; Le-Anne Bannan; Daniel K.Y. Tan; Phan Sophanara; Panhaleak Chay; Sophea Yous; et al. (Agricultural Systems, 2025)

Toward a near-lossless image compression strategy for the NASA/USGS Landsat Next mission - Rehman S. Eon; Craig De Groot; Jeffrey A. Pedelty; Aaron Gerace; Matthew Montanaro; Richard K. Covington; Amy S. DeLisa; Wen-Ting Hsieh; Joy M. Henegar-leon; Douglas J. Daniels; Christopher Engebretson; Christopher J. Crawford; et al. (Remote Sensing of Environment, 2025)

Influence of aquifer properties on optimal location and duration of groundwater level monitoring to predict aquifer recovery after mine closure - Luis Camilo Suescun; Peter Cook; Daniel Partington; Rui Hugman; Ilka Wallis (Journal of Hydrology, 2025)

Corrigendum to “Influence of aquifer properties on optimal location and duration of groundwater level monitoring to predict aquifer recovery after mine closure” [J. Hydrol. 631 (2025) 133686] - Luis Camilo Suescun; Peter Cook; Daniel Partington; Rui Hugman; Ilka Wallis (Journal of Hydrology, 2025)

Surface-based morphometry reveals divergent aging trajectories in veterans with and without traumatic brain injury - Michelle C. Eliason; Amrutha Bindu Nagella; Cristian Cuadra; David S. Wack; Ghazala T. Saleem; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowki; Arthur W. Toga; et al. (GeroScience, 2025)

Network of networks: Time series clustering of AmeriFlux sites - David E Reed; Housen Chu; Brad G. Peter; Jiquan Chen; Michael Abraha; Brian Amiro; Ray G. Anderson; M. Altaf Arain; Paulo Arruda; Greg A. Barron-Gafford; Carl Bernacchi; Daniel P. Beverly; et al. (Agricultural and Forest Meteorology, 2025)

Varying climate signals embedded in latewood blue intensity along an elevational gradient: A multi-species case study from the Great Basin, Nevada, USA - Karen E. King; Edward R. Cook; Paul J. Krusic; Daniel J. King (Dendrochronologia, 2025)

Senecio pampeanus poisoning in beef cattle: case report and toxicological evaluation - María Florencia Ovelar; Juan Agustín García; Daniel Cook; Dale Gardner; Bryan Stegelmeier; Patricia Diez de Ulzurrun; Agustina Tettamanti; Delfina Balbuena; Elvis Vilatuña Lita; Juan I. Poo; María Valeria Scioli; Germán J. Cantón (Veterinary Research Communications, 2025)

Corrigendum to article title: ‘Smallholder farmers’ challenges and opportunities: Implications for agricultural production, environment and food security’ [J. Environ. Manag., Volume: 370, Year: 2024, Pages: 122536] - Van Touch; Daniel K.Y. Tan; Brian R. Cook; De Li Liu; Rebecca Cross; Thong Anh Tran; Ariane Utomo; Sophea Yous; Clemens Grunbuhel; Annette Cowie (Journal of Environmental Management, 2025)

The Cost of Antivenom: A Cost Minimization Study using the North American Snakebite Registry - Benjamin Herzel; Neev Batavia; Paul Gavaza; Tammy Phan; Emmelyn Samones; Anne-Michelle Ruha; Jakub Furmaga; Christopher Hoyte; Brian J. Wolk; Peter Akpunonu; Adam Algren; Alexandra Amaducci; et al. (Journal of Medical Toxicology, 2025)
Envenomation is a global health issue, with over 9,000 encounters managed in the United States yearly. The introduction of immunoglobulin fragment antivenom has reduced the risk of hypersensitivity. This study compares treatment costs of crotaline envenomation using the Fab and F(ab’) 2 antivenoms as reported to the North American Snakebite Registry (NASBR), a nationwide surveillance tool. Methods This was a retrospective analysis of NASBR data between 2018 and 2020. The following data points were assessed: patient demographics (age, gender, race), snake species, type of antivenom used, and treatment costs. Unit costs were estimated based on United States Centers for Medicare and Medicaid Services data. Average (mean) per patient costs from the payer perspective were calculated by multiplying resources by the unit costs. Sensitivity analyses were performed regarding cost variance and snake species. All costs reported in this study are in U.S. dollars. Results The average total cost of treatment was $31,343 per person, with medications contributing 72% of the total. Average total cost among patients who received Fab treatments was $33,347 per person compared to $19,747 among patients who received F(ab’) 2 . Antivenom costs accounted for 75% of the total cost in the Fab group and 42% in the F(ab’) 2 group. F(ab’) 2 required more vials than Fab (median 18 versus 10). Non-antivenom costs such as hospitalizations were higher in the F(ab’) 2 group. Using average sale prices increased average total cost to $52,572; Fab remained more expensive. Conclusion Antivenom is the primary cost driver in snakebite treatment in North America. Treatment with F(ab’) 2 resulted in lower overall costs, driven by lower cost of antivenom. F(ab’) 2 did not significantly lower overall resource use except for blood product administration.

Correcting the heartwood-sapwood transition in blue intensity measurements with change point detection methods - Hung T.T. Nguyen; Rory Abernethy; Rob Wilson; Daniel L. Druckenbrod; Kathryn J. Allen; Brendan M. Buckley; Edward R. Cook; Rosanne D’Arrigo; Jonathan G. Palmer (Dendrochronologia, 2025)

Cross-cultural evidence that intergroup conflict heightens preferences for dominant leaders: A 25-country study - Lasse Laustsen; Xiaotian Sheng; M. Ghufran Ahmad; Laith Al-Shawaf; Benjamin Banai; Irena Pavela Banai; Michael Barlev; Nicolas Bastardoz; Alexander Bor; Joey T. Cheng; Anna Chmielińska; Alexandra Cook; et al. (Evolution and Human Behavior, 2025)

Practical considerations for the optimization of in situ mineralization of perfluorocarboxylic acids and polyfluoroalkyl substances using persulfate oxidation - Emily K. Cook; Christopher I. Olivares; Yilu Sun; Fuhar Dixit; Daniel Ocasio; Shan Yi; David L. Sedlak; Lisa Alvarez-Cohen (Water Research, 2025)

Systemic toxicity after rattlesnake envenomation in patients using angiotensin converting enzyme inhibitors: A North American Snakebite Registry study - A.M. Ruha; M.B. Spyres; R. Culbreth; B. Wolk; C. Hoyte; S. Campleman; Peter Akpunonu; Adam Algren; Alexandra Amaducci; Sukhshant Atti; Connie Aubin; Kevin Baumgartner; et al. (Toxicon, 2025)

Voxel-wise insights into early Alzheimer’s disease pathology progression: the association with APOE and memory decline - Maha Wybitul; Nicolas Langer; Christoph Hock; Anton Gietl; Valerie Treyer; Michael Weiner; Paul Aisen; Ronald-Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; et al. (GeroScience, 2025)
Longitudinal investigation of the Apolipoprotein E (APOE) genotype’s impact on Alzheimer’s disease (AD) biomarker progression, focusing on amyloid beta (Aβ) accumulation and gray matter (GM) atrophy, integrating cognitive decline and baseline levels. Longitudinal florbetapir-PET and T1-weighted MRI data from 100 cognitively normal (CN) and mild cognitive impaired (MCI) participants both with considerable global Aβ accumulation (“high Aβ accumulators”) were analyzed using a voxel-wise approach. Associations of APOE genotype and memory decline with Aβ accumulation and GM atrophy were examined separately for each neuroimaging modality, controlling for baseline Aβ levels and diagnosis. Alternatively, the effect of baseline diagnosis, while controlling for memory decline, was investigated. A multimodal analysis evaluated interactions between genotype, memory decline, and GM atrophy on Aβ accumulation. High Aβ accumulators displayed extensive Aβ pathology predominantly in the medial orbito-frontal cortex, cingulate cortex, and precuneus, along with GM atrophy in temporal, occipital, orbito-frontal, and parietal areas. ɛ4 carriers with memory decline exhibited greater Aβ accumulation and GM atrophy in selective regions compared to non-carriers with memory decline, while no genotype difference was observed in individuals without decline. No interaction effect was observed for MCI diagnosis. Regional associations between the two biomarkers were similarly dependent on genotype and memory decline. ɛ4 carriers exhibiting memory decline present an accelerated neurobiological pattern at predementia stages, supporting early ɛ4 carrier monitoring and interventions in this at-risk group. Importantly, memory decline might be more informative than MCI regarding AD pathology progression emphasizing the importance of repeated cognitive assessments.

DNA data (genome skims and metabarcodes) paired with chemical data demonstrate utility for retrospective analysis of forage linked to fatal poisoning of cattle - Daniel Cook; Brandon Kocurek; Clint Stonecipher; Kevin D. Welch; Dale R. Gardner; Mark Mammel; Elizabeth Reed; Padmini Ramachandran; David Erickson; Seth Commichaux; Andrea Ottesen (Toxicon, 2025)

Status of truffle science and cultivation in North America - Mark D. Coleman; Shannon Berch; Gregory Bonito; Brian Allen; Ellie Andrews; Elva T. Arechiga Carvajal; Stephen P. Cook; Cameron D’Amours; Roberto Garibay-Orijel; Gonzalo Guevara; Patrick Hatzenbuehler; Barbara Hawkins; et al. (Plant and Soil, 2025)
Background Truffles are subterranean fungal fruiting bodies that are highly prized for their culinary value. Cultivation of truffles was pioneered in Europe and has been successfully adapted in temperate regions throughout the globe. Truffle orchards have been established in North America since the 1980s, and while some are productive, there are still many challenges that must be overcome to develop a viable North American truffle industry. These challenges include extended delays between establishment and production, comparatively low yields, high spatial heterogeneity in yield distribution, and orchard contamination with lower-value truffle fungi. Aim Here we review known requirements for truffle production including necessary environmental conditions, reproductive biology, and effective agronomic practices. Content We consider the potential limitations of importing exotic host-fungal associations into North America where there is already a rich community of competing ectomycorrhizal fungi, host pests and pathogens. We also describe the status of the North American truffle industry with respect to market potential, including production costs, pricing, and biological and socioeconomic risk factors. A critical aspect of modern trufficulture involves monitoring with genetic tools that supply information on identity, abundance and distribution of fungal symbionts, abundance of competitive and contaminating fungi, and insight into the interactions between fungal mating types that are fundamental to the formation of truffle primordia. Implications Cultivation of the ectomycorrhizal truffle symbiosis requires application of pragmatic agronomic practices, adopting rigorous quality control standards, and an understanding of fungal biology, microbiology, and molecular biology. Consequently, significant interdisciplinary collaboration is crucial to further develop the North American truffle industry.

Reversal of practical resistance in fall armyworm to Cry1F maize: a case report on the resistance to susceptibility in Bt crops from the southeastern USA - Tiago Silva; Gregory A. Sword; Andie Miller; Jawwad A. Qureshi; Graham P. Head; Dawson D. Kerns; Juan Luis Jurat-Fuentes; James Villegas; Tyler B. Towles; Xinzhi Ni; Francis P. F. Reay-Jones; Daniel Carrillo; et al. (Journal of Pest Science, 2025)

Identifying resilient areas for seagrass restoration by integrating suitability modelling and climate forecasting - Oliver Dalby; Mary A. Young; Emma L. Jackson; Yi Mei Tan; Rhys A. Coleman; Kathy Cinque; Peter Yeates; Perran Cook; Peter I. Macreadie; Daniel Ierodiaconou; Craig D.H. Sherman (Estuarine, Coastal and Shelf Science, 2025)

Dynamic proportional loss of functional connectivity revealed change of left superior frontal gyrus in subjective cognitive decline: an explanatory study based on Chinese and Western cohorts - Luyao Wang; Wenjing Hu; Fan Dong; Can Sheng; Jinglong Wu; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2025)

SNAPSHOT USA 2019–2023: The First Five Years of Data From a Coordinated Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Benjamin R. Goldstein; Christopher Pate; Paula Castiblanco; Maggie E. Abell; Jessie Adley; Briana Agenbroad; Adam A. Ahlers; Peter D. Alexander; et al. (Global Ecology and Biogeography, 2025)
Motivation SNAPSHOT USA is an annual, multicontributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2019–2023 contains 987,979 records of camera trap image sequence data and 9694 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in all 50 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1st August and 29th December each year from 2019 to 2023. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2019–2023 comprises two .csv files. The original data can be found within the SNAPSHOT USA Initiative in the Wildlife Insights platform.

The actions of varenicline on alkaloids from Conium maculatum (poison hemlock), Lupinus sulphureus (sulphur lupine) and Nicotiana glauca (tree tobacco) - Benedict T. Green; Stephen T. Lee; Kevin D. Welch; Daniel Cook; Clinton A. Stonecipher (Toxicon, 2024)

The evaluation of earwax as a noninvasive specimen to determine livestock exposure to death camas (Zigadenus paniculatus) - Stephen T. Lee; Clinton A. Stonecipher; Kevin D. Welch; Daniel Cook (Toxicon, 2024)

Growth trends of loblolly pine age five or less in relation to soil type and management intensity - Christen Beasley; David R. Carter; Timothy J. Albaugh; David Enemo; Daniel S. Hong; Rachel Cook; Otávio Campoe; Rafael Rubilar (Forest Ecology and Management, 2024)

New insights to be gained from a Virtual Ecosystem - Robert M. Ewers; Jacob Cook; Olivia Z. Daniel; C.David L. Orme; Vivienne Groner; Jaideep Joshi; Anna Rallings; Taran Rallings; Priyanga Amarasekare (Ecological Modelling, 2024)

Morphology of cuticular structures in the ant genus Strumigenys (Insecta: Hymenoptera: Formicidae) - Landin Nelson; Daniel S. Doucet; Jerry L. Cook (Zoomorphology, 2024)

Smallholder farmers’ challenges and opportunities: Implications for agricultural production, environment and food security - Van Touch; Daniel K.Y. Tan; Brian R. Cook; De Li Liu; Rebecca Cross; Thong Anh Tran; Ariane Utomo; Sophea Yous; Clemens Grunbuhel; Annette Cowie (Journal of Environmental Management, 2024)

Avoidance and attraction responses of kittiwakes to three offshore wind farms in the North Sea - Christopher J. Pollock; Daniel T. Johnston; Philipp H. Boersch-Supan; Chris B. Thaxter; Elizabeth M. Humphreys; Nina J. O’Hanlon; Gary D. Clewley; Ewan D. Weston; Judy Shamoun-Baranes; Aonghais S. C. P. Cook (Marine Biology, 2024)
Seabird collision risk is a key concern in relation to the environmental impacts associated with offshore wind farms (OWFs). Understanding how species respond both to the wind farm itself, and individual turbines within the wind farm, is key to enabling better quantification and management of collision risk. Collision risk is of particular concern for the black-legged kittiwake, Rissa tridactyla , where modelling predicts unsustainable population level impacts. In this study 20 adult breeding kittiwakes, were tracked with GPS from Whinnyfold, Scotland (57°23′07″N, 001°52′11″W) during the breeding season in 2021. An Avoidance-Attraction Index (AAI) was estimated at several bands within macro- and meso-scales (0–4 km from outer boundary and 0–400 m from turbines, respectively), and the Avoidance Rate (AR; used in environmental impact assessments) at macro-scale to estimate avoidance behaviour to three operational OWFs within their foraging range. One offshore wind farm and its buffer zone (0–4 km from outer boundary) was visited more frequently by the majority of tracked individuals (19/20 birds), despite being twice as far as the closest OWF (17.3 and 31.9 km respectively), whilst 10 or less individuals used the remaining two OWFs. At the most frequented OWF we found macro-scale attraction to the closest band (0–1 km) trending towards avoidance in the furthest band (3–4 km). At the meso-scale we found avoidance of areas below the rotor height range (RHR, a.k.a. rotor swept area/zone) up to 120 m from individual turbines, which decreased to 60 m when within the RHR. Our results indicate that kittiwakes may be slightly attracted to the area around OWFs or aggregate here due to displacement but avoid individual turbines. Increased productivity in the OWF area may potentially be drawing birds into the general area, with aversion to individual turbines being responsible for meso-scale observations.

Complementary value of molecular, phenotypic, and functional aging biomarkers in dementia prediction - Andreas Engvig; Karl Trygve Kalleberg; Lars T. Westlye; Esten Høyland Leonardsen; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; et al. (GeroScience, 2024)
DNA methylation age (MA), brain age (BA), and frailty index (FI) are putative aging biomarkers linked to dementia risk. We investigated their relationship and combined potential for prediction of cognitive impairment and future dementia risk using the ADNI database. Of several MA algorithms, DunedinPACE and GrimAge2, associated with memory, were combined in a composite MA alongside BA and a data-driven FI in predictive analyses. Pairwise correlations between age- and sex-adjusted measures for MA (aMA), aBA, and aFI were low. FI outperformed BA and MA in all diagnostic tasks. A model including age, sex, and aFI achieved an area under the curve (AUC) of 0.94 for differentiating cognitively normal controls (CN) from dementia patients in a held-out test set. When combined with clinical biomarkers (apolipoprotein E ε4 allele count, memory, executive function), a model including aBA and aFI predicted 5-year dementia risk among MCI patients with an out-of-sample AUC of 0.88. In the prognostic model, BA and FI offered complementary value (both β s 0.50). The tested MAs did not improve predictions. Results were consistent across FI algorithms, with data-driven health deficit selection yielding the best performance. FI had a stronger adverse effect on prognosis in males, while BA’s impact was greater in females. Our findings highlight the complementary value of BA and FI in dementia prediction. The results support a multidimensional view of dementia, including an intertwined relationship between the biomarkers, sex, and prognosis. The tested MA’s limited contribution suggests caution in their use for individual risk assessment of dementia.

Moths respond to key habitat structures in conifer plantations managed as irregular high forest - Patrick Cook; Lisbeth Hordley; Daniel Alder; Katie Powell; David Pengelly (Forest Ecology and Management, 2024)

The Toxicology Investigators Consortium 2023 Annual Report - Adrienne Hughes; Alexandra Amaducci; Sharan L. Campleman; Shao Li; Mari Costantini; Meghan B. Spyres; Hannah Spungen; Jessica Kent; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; et al. (Journal of Medical Toxicology, 2024)

Extensive Local Geographic Variation in Locoweed Toxin Produced by a Fungal Endophyte - Jeremy Davis; Matthew Scott; Daniel Cook; Dale Gardner; Geoffrey Morse; Michael Grillo (Journal of Chemical Ecology, 2024)

Local molecular and connectomic contributions of tau-related neurodegeneration - Fardin Nabizadeh; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; Robert C. Green; Andrew J. Saykin; John Morris; et al. (GeroScience, 2024)

The use of earwax to determine livestock exposure to teratogenic lupine - Clinton A. Stonecipher; Stephen T. Lee; Kevin D. Welch; Kristian R. Valles; Daniel Cook (Toxicon, 2024)

Comparison of the acute toxicity of zygacine versus zygadenine - Kevin D. Welch; Dale R. Gardner; Stephen T. Lee; Clint A. Stonecipher; Daniel Cook (Toxicon, 2024)

A review on mycotoxins and mycotoxicoses in ruminants and Equidae in South America - Franklin Riet-Correa; Daniel Cook; Juan F. Micheloud; Mizael Machado; Fabio S. Mendonça; Ana Lucia Schild; Ricardo Amaral Lemos (Toxicon, 2024)

Japanese Yew (Taxus) poisoning of wild ungulates in Utah during the winter of 2022–2023 - Stephen T. Lee; Jane Kelly; Virginia Stout; Sydney Lamb; Thomas J. Baldwin; Daniel Cook (Toxicon, 2024)

Detrending tree-ring widths in closed-canopy forests for climate and disturbance history reconstructions - Daniel L. Druckenbrod; Edward R. Cook; Neil Pederson; Dario Martin-Benito (Dendrochronologia, 2024)

Investigating the physiological ecology of mesopelagic zooplankton in the Scotia sea (Southern ocean) using lipid and stable isotope signatures - Eloïse Linda-Roselyne Savineau; Kathryn B. Cook; Sabena J. Blackbird; Gabriele Stowasser; Konstadinos Kiriakoulakis; Calum Preece; Sophie Fielding; Anna C. Belcher; George A. Wolff; Geraint A. Tarling; Daniel J. Mayor (Deep Sea Research Part I: Oceanographic Research Papers, 2024)

Acute death as a result of poisoning tropical (Bos taurus indicus) but not temperate (Bos taurus taurus) cattle after oral dosing with Lupinus leucophyllus (velvet lupine) - Benedict T. Green; Kevin D. Welch; Stephen T. Lee; T. Zane Davis; Clinton A. Stonecipher; Bryan L. Stegelmeier; Daniel Cook (Toxicon, 2024)

Consequences of pollen defense compounds for pollinators and antagonists in a pollen‐rewarding plant - Sébastien Rivest; Stephen T. Lee; Daniel Cook; Jessica R. K. Forrest (Ecology, 2024)
Plants produce an array of defensive compounds with toxic or deterrent effects on insect herbivores. Pollen can contain relatively high concentrations of such defense compounds, but the causes and consequences of this enigmatic phenomenon remain mostly unknown. These compounds could potentially protect pollen against antagonists but could also reduce flower attractiveness to pollinators. We combined field observations of the pollen‐rewarding Lupinus argenteus with chemical analysis and laboratory assays to test three hypotheses for the presence of pollen defense compounds: (1) these compounds are the result of spillover from adjacent tissues, (2) they protect against pollen thieves, and (3) they act as antimicrobial compounds. We also tested whether pollen defense compounds affect pollinator behavior. We found a positive relationship between alkaloid concentrations in pollen and petals, supporting the idea that pollen defense compounds partly originate from spillover. However, pollen and petals exhibited quantitatively (but not qualitatively) distinct alkaloid profiles, suggesting that plants can adjust pollen alkaloid composition independently from that of adjacent tissues. We found no relationship between pollen alkaloid concentration and the abundance of pollen thieves in Lupinus flowers. However, pollen alkaloids were negatively associated with bacterial abundance. Finally, plants with more alkaloids in their pollen received more pollinator visits, but these visits were shorter, resulting in no change in the overall number of flowers visited. We propose that pollen defense compounds are partly the result of spillover from other tissues, while they also play an antimicrobial role. The absence of negative effects of these compounds on pollinator visitation likely allows their maintenance in pollen at relatively high concentrations. Taken together, our results suggest that pollen alkaloids affect and are mediated by the interplay of multiple interactions.

Sex differences in interacting genetic and functional connectivity biomarkers in Alzheimer’s disease - Jordan N. Williamson; Shirley A. James; Sean P. Mullen; Bradley P. Sutton; Tracey Wszalek; Beni Mulyana; Peter Mukli; Andriy Yabluchanskiy; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2024)

Ruminant metabolism of zygacine, the major toxic alkaloid in foothill death camas (Zigadenus paniculatus) - Stephen T. Lee; Clinton A. Stonecipher; Benedict T. Green; Kevin D. Welch; Dale R. Gardner; Daniel Cook (Toxicon, 2024)

Cecal dilatation in cattle ingesting Megathyrsus maximus (syn. Panicum maximum) cv. Mombaça and cv. Tanzânia - Sandro V. Schons; Taciane Leticia de Melo Souza; Jeronimo Vieira Dantas Filho; Elvino Ferreira; Ed Johnny da Rosa Prado; James Pfister; Daniel Cook; Franklin Riet-Correa (Toxicon, 2024)

The influence of the toxin-producing dinoflagellate, Alexandrium catenella, on feeding, reproduction and toxin retention in Calanus helgolandicus - Ali H. Abdulhussain; Kathryn B. Cook; Eileen Bresnan; Jean-Pierre Lacaze; Daniel J. Mayor (Harmful Algae, 2024)

Unveiling the phenotypic landscape of stalk lodging resistance in diverse maize hybrids - Bharath Kunduru; Rohit Kumar; Manwinder S. Brar; Christopher J. Stubbs; Kaitlin Tabaracci; Norbert T. Bokros; William C. Bridges; Douglas D. Cook; Seth DeBolt; Christopher S. McMahan; Daniel J. Robertson; Rajandeep S. Sekhon (Field Crops Research, 2023)

The Toxicology Investigators Consortium 2022 Annual Report - Alexandra M. Amaducci; Sharan L. Campleman; Shao Li; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; Rachel E. Culbreth; Paul M. Wax; Jeffrey Brent; Kim Aldy; Jennifer Acciani; et al. (Journal of Medical Toxicology, 2023)

Seeing the wood for the trees, irregular silviculture supports bat populations in conifer plantations - Patrick Cook; Daniel Alder; Lisbeth Hordley; Stuart E. Newson; David Pengelly (Forest Ecology and Management, 2023)

Rotation-age effects of subsoiling, fertilization, and weed control on radiata pine growth at sites with contrasting soil physical, nutrient, and water limitations - Rafael Rubilar; Daniel Bozo; Timothy Albaugh; Rachel Cook; Otávio Campoe; David Carter; H. Lee Allen; José Álvarez; Matías Pincheira; Álvaro Zapata (Forest Ecology and Management, 2023)

Moving toward short stature maize: The effect of plant height on maize stalk lodging resistance - Christopher J. Stubbs; Bharath Kunduru; Norbert Bokros; Virginia Verges; Jordan Porter; Douglas D. Cook; Seth DeBolt; Christopher McMahan; Rajandeep S. Sekhon; Daniel J. Robertson (Field Crops Research, 2023)

Glucose metabolism in posterior cingulate cortex has supplementary value to predict the progression of cognitively unimpaired to dementia due to Alzheimer’s disease: an exploratory study of 18F-FDG-PET - Qi Zhang; Chunqiu Fan; Luyao Wang; Taoran Li; Min Wang; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2023)

Carbon budgets of Scotia Sea mesopelagic zooplankton and micronekton communities during austral spring - Kathryn B. Cook; Anna Belcher; Daniel Bondyale Juez; Gabriele Stowasser; Sophie Fielding; Ryan A. Saunders; Mohamed A. Elsafi; George A. Wolff; Sabena J. Blackbird; Geraint A. Tarling; Daniel J. Mayor (Deep Sea Research Part II: Topical Studies in Oceanography, 2023)

Adaptation constraints and prospects for future research priorities in lowland rice-based farming systems: learning experiences from Northwest Cambodia - Van Touch; Rebecca Cross; Clemens Grünbühel; Floris Van Ogtrop; Peter Ampt; Try Yorn; Robert John Martin; Brian R. Cook; Daniel K. Y. Tan (Environment, Development and Sustainability, 2023)
Sustainable agricultural development not only addresses global food insecurity but may also alleviate poverty by enriching the lives of millions of smallholder farmers. Improving the sustainability and profitability of agriculture where smallholders are dominant creates profound impacts because small landholding farmers produce approximately 70–80% of the global food. The need for a thorough understanding of the factors affecting farmers’ adoption of agricultural technologies and practices has been identified from extant literature as an important research gap. Responding to the research gap and need, this study examined the challenges that prevent farm households from adopting improved farming practices and/or technologies in Banteay Meanchey and Battambang provinces in Northwest Cambodia. A total of 524 rice producing farm household representatives were randomly selected from a household database maintained by the local government authorities. A mixed methods approach was used in the study including semi-structured interviews followed by in-depth interviews, field observations, and literature review. Farmers were found to be confronted with a range of challenges and concerns, including soil degradation, weeds, diseases, insect pests, high production costs, flooding, droughts, changing rainfall pattern, and unreliable rainfall distribution. The research findings demonstrate that improved crop production practices (e.g., adopting mechanised direct seeding methods of crop establishment, maintaining and improving soil health through crop residue retention, growing cover crops, etc.) and better resource use efficiency (e.g., reducing seeding rates to less than 100 kg/ha, being more strategic in the use of integrated nutrient, weed, and pest management strategies, etc.) can be a starting point for sustainable intensification of rice production. This transition towards intensifying paddy production sustainably may become even more effective through a clear understanding of local contexts, farm household characteristics, available resources, and the farm management practices and constraints. We observed that farmers and their associations have yet to be fully recognised as partners and actors in Cambodia. Instead, they tend to be viewed as beneficiaries and recipients of improved practices and technologies. We, therefore, propose that farmers and their associations be acknowledged and included in a process of co-creation of knowledge-practices. Such partnerships will enable the inclusion of factors (e.g., production costs, production risks, complexity and practicability of implementations, product market and prices, etc.) shown to influence farmers’ adoption of innovative farming practices and technologies. The original contribution of this article is a real-world account of the constraints and limitations experienced by smallholder rice farmers in Cambodia, which are connected to future research and development priorities in the region.

Toxic plants from the perspective of a “Quilombola” community in the Cerrado region of Brazil - Ricardo de Castro Santos Paim; Luiza Gabriella Ferreira de Paula; Débora Moreira Soares; Tarik Fernandes Gonçalves Rocha; Amanda Lopes Ribeiro; Natália Barros; Fabrício Carrião dos Santos; Heleno Dias Ferreira; Vera Lúcia Gomes-Klein; Benito Soto-Blanco; José Paes de Oliveira-Filho; Paulo Henrique Jorge da Cunha; et al. (Toxicon, 2023)

Long-term monitoring reveals the impact of changing climate and habitat on the fitness of cavity-nesting songbirds - Jason Riggio; Andrew Engilis; Hanika Cook; Evelien de Greef; Daniel S. Karp; Melanie L. Truan (Biological Conservation, 2023)

Assay measurement of gaseous UF6 using femtosecond laser-induced breakdown spectroscopy in the 424.4 nm spectral region - Benjamin S. Jordan; Jason D. Readle; Jeffrey R. Cooper; Matthew Cook; Jason P. Hayward; J. Daniel Hartman; Dean Forrest; Howard L. Hall (Annals of Nuclear Energy, 2023)

The Toxicology Investigators Consortium Case Registry—the 2021 Annual Report - Jennifer S. Love; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; HoanVu Nguyen; Sharan L. Campleman; Shao Li; Paul M. Wax; Jeffery Brent; Kim Aldy; Michael Abesamis; et al. (Journal of Medical Toxicology, 2022)

Grazing, egg production and carbon budgets for Calanus finmarchicus across the Fram Strait - Holly E. Jenkins; Florence Atherden; Kathryn B. Cook; Thomas R. Anderson; Barry Thornton; Elaine Mitchell; Elodie Jacob; Daniel J. Mayor (Frontiers in Marine Science, 2022)
Calanoid copepods comprise around 90% of Arctic zooplankton biomass and are fundamental to the ecological and biogeochemical functioning of high-latitude pelagic ecosystems. They accumulate lipid reserves during the productive months and represent an energy-rich food source for higher trophic levels. Rapidly changing climate in the Arctic may alter the quantity and composition of the food environment for one of the key copepod species, Calanus finmarchicus , with as yet unquantified effects on its production. Here we present rates of feeding and egg production in female C. finmarchicus exposed to the range of feeding conditions encountered across the Fram Strait in May/June 2018. Carbon (C) budgets were constructed and used to examine the relationship between feeding and growth (= egg production) in these animals. C-specific ingestion rates (mean ± standard deviation) were highly variable, ranging from 0.015 ± 0.004 to 0.645 ± 0.017 day -1 (mean = 0.295 ± 0.223 day -1 ), and were positively correlated with food availability. C-specific egg production rates ranged from 0.00 to 0.049 day -1 (mean = 0.012 ± 0.011) and were not correlated with either food availability or ingestion rate. Calculated gross growth efficiencies (GGE: growth/ingestion) were low, 0.12 ± 0.13 (range = 0.01 to 0.39). The assembled C budgets indicate that the average fraction of ingested food that was surplus to the requirements for egg production, respiration and losses to faecal pellets was 0.17 ± 0.42. We suggest that this excess occurred, at least in part, because many of the incubated females were still undergoing the energetically (C-) expensive process of gonad maturation at the time of sampling, an assertion that is supported by the relatively high C:N (nitrogen) ratios of the incubated females, the typically low egg production rates, and gonad maturation status. Ontogenetic development may thus explain the large variability seen in the relationship between egg production and ingestion. The apparently excessive ingestion rates may additionally indicate that recently moulted females must acquire additional N via ingestion to complete the maturation process and begin spawning. Our results highlight the need for improved fundamental understanding of the physiology of high-latitude copepods and its response to environmental change.

Glucose metabolism patterns: A potential index to characterize brain ageing and predict high conversion risk into cognitive impairment - Jiehui Jiang; Can Sheng; Guanqun Chen; Chunhua Liu; Shichen Jin; Lanlan Li; Xueyan Jiang; Ying Han; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2022)

Red Pigmentation Can Be Used to Reliably Distinguish Between Live Calanus finmarchicus and Calanus glacialis Females in the Fram Strait - Penelope K. Lindeque; Isabelle Hann; Helen E. Parry; Kathryn B. Cook; Anthony J. W. Lindley; Daniel J. Mayor (Frontiers in Marine Science, 2022)
Copepods from the genus Calanus provide an important lipid-rich food source in the Arctic marine foodweb. Despite extensive research on Calanus finmarchicus and Calanus glacialis , accurately identifying adults to species level remains challenging due to similar morphologies. Although these species co-occur in many regions, the distribution of C. finmarchicus and C. glacialis correspond to Atlantic and Arctic water masses respectively and are frequently used as climate indicators. Correct identification is therefore vital for understanding the phenotypic plasticity of these species and the impacts climate change will have on Calanus- dominated marine ecosystems. In this study, prosome length and percentage of red pigmentation (redness) of genital somites, the antennae, and throughout the whole body were determined for 139 females of C. finmarchicus and C. glacialis from the Fram Strait. Molecular analysis of a 16S rDNA barcode confirmed that the best morphological features for resolving the identity of these two species were the redness of the antennae and the redness of the genital somites. Overall accuracy of using antennae redness and genital somite redness to discriminate between the two species were the same, yet each of these explanatory variables had different specificity; C. finmarchicus were more accurately identified by the absence of redness in the genital somites, whereas C. glacialis were more accurately identified using antennae redness. Given the ecological importance of these congeners, these findings contribute to a better understanding of the reliability of using morphological characteristics to identify Calanus to species level, especially when sorting live specimens for climate-related ecological experiments.

Carbon and Lipid Contents of the Copepod Calanus finmarchicus Entering Diapause in the Fram Strait and Their Contribution to the Boreal and Arctic Lipid Pump - Geraint A. Tarling; Anna Belcher; Mayleen Blackwell; Claudia Castellani; Kathryn Barbara Cook; Finlo R. Cottier; Victoria Dewar-Fowler; Jennifer J. Freer; Laura Gerrish; Magnus L. Johnson; Kim S. Last; Penelope Kate Lindeque; et al. (Frontiers in Marine Science, 2022)
The boreal copepod Calanus finmarchicus sequesters substantial amounts of carbon (C) in the deep layers of the North Atlantic Ocean through their contribution to the “lipid pump.” This pump is driven by these zooplankton descending from the surface layers to spend prolonged periods at depth during which time they metabolise substantial lipid reserves and a fraction suffer mortality. C. finmarchicus is principally a boreal species but is expatriated by currents flowing northwards into Arctic regions such as the Fram Strait, where it is now able to complete its life cycle. We considered how this expansion to its distributional range adds to the estimated magnitude of the lipid pump. Field sampling in the Fram Strait found C. finmarchicus abundance to be spatially variable with high values, equivalent to those reported for core distributional areas further south, found mainly in the eastern region. Lipid reserve levels were sufficient for many individuals to survive the overwintering period and reproduce the following spring. In accordance with abundance patterns, lipid pump magnitude was greater in the Eastern Fram Strait (2.04 g C m −2 year −1 ) compared to the Western Fram Strait (0.33 g C m −2 year −1 ). At least for the eastern region, these rates are similar to those reported for this species elsewhere (average of 4.35 g C m −2 year −1 ). When extrapolated to the wider spatial area of the Fram Strait, the lipid pump generated by this species in this ocean sector amounts to 0.3 Mt C year −1 . Although constituting a modest proportion of the total C. finmarchicus lipid pump of 19.3 Mt C year −1 , it indicates that the continued northwards expansion of this species will act to increase the size of its lipid pump, which may counteract that lost through the northwards retreat of its Arctic congeners, Calanus glacialis and Calanus hyperboreus .

Biomass Turnover Rates in Metabolically Active and Inactive Marine Calanoid Copepods - Daniel J. Mayor; Kathryn B. Cook; Barry Thornton; Florence Atherden; Geraint A. Tarling; Thomas R. Anderson (Frontiers in Marine Science, 2022)
Lipid-storing copepods are fundamental to the functioning of marine ecosystems, transferring energy from primary producers to higher trophic levels and sequestering atmospheric carbon (C) in the deep ocean. Quantifying trophic transfer and biogeochemical cycling by copepods requires improved understanding of copepod metabolic rates in both surface waters and during lipid-fueled metabolism over winter. Here we present new biomass turnover rates of C and nitrogen (N) in Calanoides acutus , Calanoides natalis , Calanus glacialis and Calanus hyperboreus alongside published data for Calanus finmarchicus and Calanus pacificus . Turnover rates in metabolically active animals, normalised to 10°C, ranged between 0.007 – 0.105 d -1 and 0.004 – 0.065 d -1 for C and N, respectively. Turnover rates of C were typically faster than those for N, supporting the understanding that non-protein C, e.g. lipid, is catabolised faster than protein. Re-analysis of published data indicates that inactive, overwintering C. finmarchicus turn over wax ester lipids at a rate of 0.0016 d -1 . These and other basal rate data will facilitate the mechanistic representation of copepod physiology in global biogeochemical models, thereby reducing uncertainties in our predictions of future ocean ecosystem functioning and C sequestration.

Comprehensive analysis of epigenetic clocks reveals associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Tenielle Porter; Vincent Doré; Samantha C. Burnham; Pierrick Bourgeat; Rosita Shishegar; James Doecke; Nicola J. Armstrong; Rick Tankard; Paul Maruff; Colin L. Masters; et al. (GeroScience, 2022)
The concept of age acceleration, the difference between biological age and chronological age, is of growing interest, particularly with respect to age-related disorders, such as Alzheimer’s Disease (AD). Whilst studies have reported associations with AD risk and related phenotypes, there remains a lack of consensus on these associations. Here we aimed to comprehensively investigate the relationship between five recognised measures of age acceleration, based on DNA methylation patterns (DNAm age), and cross-sectional and longitudinal cognition and AD-related neuroimaging phenotypes (volumetric MRI and Amyloid-β PET) in the Australian Imaging, Biomarkers and Lifestyle (AIBL) and the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Significant associations were observed between age acceleration using the Hannum epigenetic clock and cross-sectional hippocampal volume in AIBL and replicated in ADNI. In AIBL, several other findings were observed cross-sectionally, including a significant association between hippocampal volume and the Hannum and Phenoage epigenetic clocks. Further, significant associations were also observed between hippocampal volume and the Zhang and Phenoage epigenetic clocks within Amyloid-β positive individuals. However, these were not validated within the ADNI cohort. No associations between age acceleration and other Alzheimer’s disease-related phenotypes, including measures of cognition or brain Amyloid-β burden, were observed, and there was no association with longitudinal change in any phenotype. This study presents a link between age acceleration, as determined using DNA methylation, and hippocampal volume that was statistically significant across two highly characterised cohorts. The results presented in this study contribute to a growing literature that supports the role of epigenetic modifications in ageing and AD-related phenotypes.

The Open-Ocean Gulf of Mexico After Deepwater Horizon: Synthesis of a Decade of Research - Tracey T. Sutton; Rosanna J. Milligan; Kendra Daly; Kevin M. Boswell; April B. Cook; Maëlle Cornic; Tamara Frank; Kaitlin Frasier; Daniel Hahn; Frank Hernandez; John Hildebrand; Chuanmin Hu; et al. (Frontiers in Marine Science, 2022)
The scale of the Deepwater Horizon disaster was and is unprecedented: geographic extent, pollutant amount, countermeasure scope, and of most relevance to this Research Topic issue, range of ecotypes affected. These ecotypes include coastal/nearshore, continental shelf, deep benthic, and open-ocean domains, the last of which is the subject of this synthesis. The open-ocean ecotype comprises ~90% of the volume of the Gulf of Mexico. The exact percentage of this ecotype contaminated with toxins is unknown due to its three-dimensional nature and dynamics, but estimates suggest that the footprint encompassed most of its eastern half. Further, interactions between the water column and the deep benthos may be persistent, making this synthesis one of time (a decade) rather than event conclusion. Here we examine key elements of the open-ocean ecosystem, with emphasis on vulnerability and resilience. Of paramount importance relative to the Gulf nearshore and shelf ecotypes, pre-disaster baseline data were lacking for most of the fauna. In such cases, inferences were drawn from post-disaster assessments. Both phytoplankton and mesozooplankton vulnerabilities were quite high, but resilience appeared equally so. The phytoplankton situation was a bit more complex in that toxin-imposed reductions may have been offset by nutrient injection via high freshwater discharge in 2010. Intermediate trophic levels exhibited population-level depressions, ostensibly due to high vulnerability and low resilience. Apex predator impacts were variable. Certain large epipelagic fishes may have avoided the highest concentrations of hydrocarbons/dispersant, and thus larval abundances returned to pre-disaster levels of variability and abundance within a few years after a steep initial decline. Oceanic cetaceans, particularly shallow-diving stenellid dolphins, did not appear to avoid oiled waters and exhibited strong declines in the northern Gulf. Given that population declines of many open-ocean taxa appear to be ongoing a decade later, we conclude that this largest of Gulf ecosystem components, like its deep-benthic counterpart, is as fragile as it is voluminous. This is particularly concerning given the rapid, and likely irreversible, shift to deeper waters by the US and Mexican oil industries in concert with the higher likelihood of accidents with increasing platform depth.

Expert range maps of global mammal distributions harmonised to three taxonomic authorities - Charles J. Marsh; Yanina V. Sica; Connor J. Burgin; Wendy A. Dorman; Robert C. Anderson; Isabel del Toro Mijares; Jessica G. Vigneron; Vijay Barve; Victoria L. Dombrowik; Michelle Duong; Robert Guralnick; Julie A. Hart; et al. (Journal of Biogeography, 2022)
Aim Comprehensive, global information on species' occurrences is an essential biodiversity variable and central to a range of applications in ecology, evolution, biogeography and conservation. Expert range maps often represent a species' only available distributional information and play an increasing role in conservation assessments and macroecology. We provide global range maps for the native ranges of all extant mammal species harmonised to the taxonomy of the Mammal Diversity Database (MDD) mobilised from two sources, the Handbook of the Mammals of the World (HMW) and the Illustrated Checklist of the Mammals of the World (CMW). Location Global. Taxon All extant mammal species. Methods Range maps were digitally interpreted, georeferenced, error‐checked and subsequently taxonomically aligned between the HMW (6253 species), the CMW (6431 species) and the MDD taxonomies (6362 species). Results Range maps can be evaluated and visualised in an online map browser at Map of Life ( mol.org ) and accessed for individual or batch download for non‐commercial use. Main conclusion Expert maps of species' global distributions are limited in their spatial detail and temporal specificity, but form a useful basis for broad‐scale characterizations and model‐based integration with other data. We provide georeferenced range maps for the native ranges of all extant mammal species as shapefiles, with species‐level metadata and source information packaged together in geodatabase format. Across the three taxonomic sources our maps entail, there are 1784 taxonomic name differences compared to the maps currently available on the IUCN Red List website. The expert maps provided here are harmonised to the MDD taxonomic authority and linked to a community of online tools that will enable transparent future updates and version control.

Local adaptation and spatiotemporal patterns of genetic diversity revealed by repeated sampling of Caenorhabditis elegans across the Hawaiian Islands - Timothy A. Crombie; Paul Battlay; Robyn E. Tanny; Kathryn S. Evans; Claire M. Buchanan; Daniel E. Cook; Clayton M. Dilks; Loraina A. Stinson; Stefan Zdraljevic; Gaotian Zhang; Nicole M. Roberto; Daehan Lee; et al. (Molecular Ecology, 2022)
The nematode Caenorhabditis elegans is among the most widely studied organisms, but relatively little is known about its natural ecology. Genetic diversity is low across much of the globe but high in the Hawaiian Islands and across the Pacific Rim. To characterize the niche and genetic diversity of C. elegans on the Hawaiian Islands and to explore how genetic diversity might be influenced by local adaptation, we repeatedly sampled nematodes over a three‐year period, measured various environmental parameters at each sampling site, and whole‐genome sequenced the C. elegans isolates that we identified. We found that the typical Hawaiian C. elegans niche comprises moderately moist native forests at high elevations (500–1,500 m) where ambient air temperatures are cool (15–20°C). Compared to other Caenorhabditis species found on the Hawaiian Islands ( e.g ., Caenorhabditis briggsae and Caenorhabditis tropicalis ), we found that C. elegans were enriched in native habitats. We measured levels of genetic diversity and differentiation among Hawaiian C. elegans and found evidence of seven genetically distinct groups distributed across the islands. Then, we scanned these genomes for signatures of local adaptation and identified 18 distinct regions that overlap with hyper‐divergent regions, which may be maintained by balancing selection and are enriched for genes related to environmental sensing, xenobiotic detoxification, and pathogen resistance. These results provide strong evidence of local adaptation among Hawaiian C. elegans and contribute to our understanding of the forces that shape genetic diversity on the most remote volcanic archipelago in the world.

Learning Together for and with the Martuwarra Fitzroy River - Rosemary Hill; Pia Harkness; Nat Raisbeck-Brown; Ilisapeci Lyons; Jorge G. Álvarez-Romero; Milena Kiatkoski Kim; Dennis Chungalla; Heather Wungundin; Mary Aiken; Jean Malay; Bernadette Williams; Rachel Buissereth; et al. (Sustainability Science, 2022)
Co-production across scientific and Indigenous knowledge systems has become a cornerstone of research to enhance knowledge, practice, ethics, and foster sustainability transformations. However, the profound differences in world views and the complex and contested histories of nation-state colonisation on Indigenous territories, highlight both opportunities and risks for Indigenous people when engaging with knowledge co-production. This paper investigates the conditions under which knowledge co-production can lead to improved Indigenous adaptive environmental planning and management among remote land-attached Indigenous peoples through a case study with ten Traditional Owner groups in the Martuwarra (Fitzroy River) Catchment in Western Australia’s Kimberley region. The research team built a 3D map of the river and used it, together with an interactive table-top projector, to bring together both scientific and Indigenous spatial knowledge. Participatory influence mapping, aligned with Traditional Owner priorities to achieve cultural governance and management planning goals set out in the Fitzroy River Declaration, investigated power relations. An analytical framework, examining underlying mechanisms of social learning, knowledge promotion and enhancing influence, based on different theories of change, was applied to unpack the immediate outcomes from these activities. The analysis identified that knowledge co-production activities improved the accessibility of the knowledge, the experiences of the knowledge users, strengthened collective identity and partnerships, and strengthened Indigenous-led institutions. The focus on cultural governance and management planning goals in the Fitzroy River Declaration enabled the activities to directly affect key drivers of Indigenous adaptive environmental planning and management—the Indigenous-led institutions. The nation-state arrangements also gave some support to local learning and decision-making through a key Indigenous institution, Martuwarra Fitzroy River Council. Knowledge co-production with remote land-attached Indigenous peoples can improve adaptive environmental planning and management where it fosters learning together, is grounded in the Indigenous-led institutions and addresses their priorities.

Can a key boreal Calanus copepod species now complete its life-cycle in the Arctic? Evidence and implications for Arctic food-webs - Geraint A. Tarling; Jennifer J. Freer; Neil S. Banas; Anna Belcher; Mayleen Blackwell; Claudia Castellani; Kathryn B. Cook; Finlo R. Cottier; Malin Daase; Magnus L. Johnson; Kim S. Last; Penelope K. Lindeque; et al. (Ambio, 2022)
The changing Arctic environment is affecting zooplankton that support its abundant wildlife. We examined how these changes are influencing a key zooplankton species, Calanus finmarchicus , principally found in the North Atlantic but expatriated to the Arctic. Close to the ice-edge in the Fram Strait, we identified areas that, since the 1980s, are increasingly favourable to C. finmarchicus . Field-sampling revealed part of the population there to be capable of amassing enough reserves to overwinter. Early developmental stages were also present in early summer, suggesting successful local recruitment. This extension to suitable C. finmarchicus habitat is most likely facilitated by the long-term retreat of the ice-edge, allowing phytoplankton to bloom earlier and for longer and through higher temperatures increasing copepod developmental rates. The increased capacity for this species to complete its life-cycle and prosper in the Fram Strait can change community structure, with large consequences to regional food-webs.

Geographic variation of mercury in breeding tidal marsh sparrows of the northeastern United States - Christopher J. Sayers; Mackenzie R. Roeder; Lindsay M. Forrette; Daniel Roche; Gaetan L. B. Dupont; Sam E. Apgar; Alison R. Kocek; Alexandra M. Cook; W. Gregory Shriver; Chris S. Elphick; Brian Olsen; David N. Bonter (Ecotoxicology, 2021)

Genetic analyses of gynecological disease identify genetic relationships between uterine fibroids and endometrial cancer, and a novel endometrial cancer genetic risk region at the WNT4 1p36.12 locus - Pik Fang Kho; Sally Mortlock; Frederic Amant; Daniela Annibali; Katie Ashton; John Attia; Paul L. Auer; Matthias W. Beckmann; Amanda Black; Louise Brinton; Daniel D. Buchanan; Stephen J. Chanock; et al. (Human Genetics, 2021)

The Influence of the Toxin-Producing Dinoflagellate, Alexandrium catenella (1119/27), on the Survival and Reproduction of the Marine Copepod, Acartia tonsa, During Prolonged Exposure - Ali H. Abdulhussain; Kathryn B. Cook; Andrew D. Turner; Adam M. Lewis; Thomas S. Bibby; Daniel J. Mayor (Frontiers in Marine Science, 2021)
Copepods can feed on, and may regulate, the blooms of harmful algae (HA), and may also facilitate dinoflagellate blooms by inducing toxin production and through selective grazing. However, exposure to HA may also cause mortality and reproductive impairment in copepods, with detrimental effects at the population-scale. Here we present the toxin profile of the dinoflagellate, Alexandrium catenella (formerly Alexandrium tamarense ), and examine how it affects the survival and reproduction of the cosmopolitan marine copepod, Acartia tonsa . Healthy adult copepods were exposed to mono-specific diets of toxic and non-toxic strains of A. catenella (1119/27 and 1119/19, respectively) and non-toxic Rhodomonas sp. for 10 days alongside unfed controls to examine how their survival was influenced by likely HA bloom conditions. Additional 2-day experiments examined how their egg production rate and hatching success were affected by food deprivation, toxic A. catenella , a non-toxic alternative and a mixture of toxic and non-toxic prey, at high and low concentrations. Survival of A. tonsa declined over the 10-day experiment in all treatments but was not significantly lower in the toxic A. catenella treatment; mortality was only significantly enhanced in the unfed animals, which showed 100% mortality after 9 days. Egg production rates and hatching success from females in the unfed and toxic A. catenella treatments were all significantly lower than values observed in females fed Rhodomonas sp. or non-toxic A. catenella . Animals offered 1,000 μg C L –1 of Rhodomonas sp. and a 50:50 mixture of toxic A. catenella and Rhodomonas sp. produced significantly more eggs than animals fed toxic A. catenella alone. These results were not apparent at prey concentrations of 100 μg C L –1 . The percentages of eggs to successfully hatch from females offered mono-specific diets of toxic A. catenella were always close to zero. Collectively, our results indicate that adult female A. tonsa can acquire sufficient energy from toxic A. catenella to survive, but suffer reproductive impairment when feeding on this prey alone.

A little SNP of this, a little SNP of that: The discovery of 116 single nucleotide polymorphism markers to enable the rapid identification of individual Pacific walrus (Odobenus rosmarus divergens) - Geoffrey M. Cook; Daniel J. Prince; Sean M. O’Rourke; Timothy L. King; Michael R. Miller; Cara J. Lewis; Michael S. Eackles; Patrick R. Lemons; Suresh A. Sethi; Jeffrey B. Olsen; John K. Wenburg (Conservation Genetics Resources, 2020)

Molecular Characterization of a Fungal Ketide Synthase Gene Among Swainsonine-Producing Alternaria Species in the USA - Aziza I. Noor; Marwa Neyaz; Daniel Cook; Rebecca Creamer (Current Microbiology, 2020)

Geomorphology and geological controls of an active paraglacial rockslide in the New Zealand Southern Alps - Emma Cody; Daniel Draebing; Samuel McColl; Simon Cook; Marc-Andre Brideau (Landslides, 2020)

Bioethanol Production from UK Seaweeds: Investigating Variable Pre-treatment and Enzyme Hydrolysis Parameters - Emily T. Kostas; Daniel A. White; David J. Cook (BioEnergy Research, 2020)
This study describes the method development for bioethanol production from three species of seaweed. Laminaria digitata , Ulva lactuca and for the first time Dilsea carnosa were used as representatives of brown, green and red species of seaweed, respectively. Acid thermo-chemical and entirely aqueous (water) based pre-treatments were evaluated, using a range of sulphuric acid concentrations (0.125–2.5 M) and solids loading contents (5–25 % [w/v]; biomass: reactant) and different reaction times (5–30 min), with the aim of maximising the release of glucose following enzyme hydrolysis. A pre-treatment step for each of the three seaweeds was required and pre-treatment conditions were found to be specific to each seaweed species. Dilsea carnosa and U. lactuca were more suited with an aqueous (water-based) pre-treatment (yielding 125.0 and 360.0 mg of glucose/g of pre-treated seaweed, respectively), yet interestingly non pre-treated D. carnosa yielded 106.4 g g −1 glucose. Laminaria digitata required a dilute acid thermo-chemical pre-treatment in order to liberate maximal glucose yields (218.9 mg glucose/g pre-treated seaweed). Fermentations with S. cerevisiae NCYC2592 of the generated hydrolysates gave ethanol yields of 5.4 g L −1 , 7.8 g L −1 and 3.2 g L −1 from D. carnosa , U. lactuca and L. digitata , respectively. This study highlighted that entirely aqueous based pre-treatments are effective for seaweed biomass, yet bioethanol production alone may not make such bio-processes economically viable at large scale.

Ultra-endurance triathlon performance and markers of whole-body and gut-specific inflammation - Kyle A. Smith; Jacob N. Kisiolek; Brandon D. Willingham; Margaret C. Morrissey; Samantha M. Leyh; Patrick G. Saracino; Daniel A. Baur; Marc D. Cook; Michael J. Ormsbee (European Journal of Applied Physiology, 2020)

Toward the Integrated Marine Debris Observing System - Nikolai Maximenko; Paolo Corradi; Kara Lavender Law; Erik Van Sebille; Shungudzemwoyo P. Garaba; Richard Stephen Lampitt; Francois Galgani; Victor Martinez-Vicente; Lonneke Goddijn-Murphy; Joana Mira Veiga; Richard C. Thompson; Christophe Maes; et al. (Frontiers in Marine Science, 2019)

The state of Western Australia’s coral reefs - James P. Gilmour; Kylie L. Cook; Nicole M. Ryan; Marjetta L. Puotinen; Rebecca H. Green; George Shedrawi; Jean-Paul A. Hobbs; Damian P. Thomson; Russell C. Babcock; Joanna Buckee; Taryn Foster; Zoe T. Richards; et al. (Coral Reefs, 2019)

3D Printing of Metformin HCl PVA Tablets by Fused Deposition Modeling: Drug Loading, Tablet Design, and Dissolution Studies - Mariam Ibrahim; Morgan Barnes; Robert McMillin; Daniel W. Cook; Sarah Smith; Mathew Halquist; Dayanjan Wijesinghe; Thomas D. Roper (AAPS PharmSciTech, 2019)

Response of Scotian Shelf silver hake ( Merluccius bilinearis ) to environmental variability - Daniel Reed; Stéphane Plourde; Adam Cook; Pierre Pepin; Benoit Casault; Caroline Lehoux; Catherine Johnson (Fisheries Oceanography, 2019)
Commercially‐exploited fish populations are not only shaped by fishing pressure, but also by the dynamics of their environment. By quantifying the influence of environmental variability, fisheries management advice can be improved and uncertainties reduced. To this end, we developed statistical models of the response of Scotian Shelf silver hake stock metrics to variability in zooplankton community composition and phenology over the past 18 years and in the physical environment since 1985. Dominant modes of variability in these pelagic habitat indicators were characterized using principal component analysis, and the relationships of silver hake condition, abundance, and recruitment to pelagic habitat variability were assessed using generalized additive models. Condition was largely modulated by the onset and duration of the spring bloom, which controls food availability. In contrast, adult abundance was governed by composition of the zooplankton community and bottom‐water temperature, which dictates the distribution of silver hake. Finally, recruitment was affected by both thermal conditions and food availability. Our results presented here form the basis for qualitative assessment of ecosystem attributes and the influence on silver hake stock productivity.

Can we increase smokers’ adherence to nicotine replacement therapy and does this help them quit? - Tanya R. Schlam; Jessica W. Cook; Timothy B. Baker; Todd Hayes-Birchler; Daniel M. Bolt; Stevens S. Smith; Michael C. Fiore; Megan E. Piper (Psychopharmacology, 2018)

Using an in vitro system for maintaining Varroa destructor mites on Apis mellifera pupae as hosts: studies of mite longevity and feeding behavior - Noble I. Egekwu; Francisco Posada; Daniel E. Sonenshine; Steven Cook (Experimental and Applied Acarology, 2018)

RNAi-mediated down-regulation of a melanin polyketide synthase (pks1) gene in the fungus Slafractonia leguminicola - Mohammad S. Alhawatema; Sayed Gebril; Daniel Cook; Rebecca Creamer (World Journal of Microbiology and Biotechnology, 2017)

Effects of Elevated CO2 on the Swainsonine Chemotypes of Astragalus lentiginosus and Astragalus mollissimus - Daniel Cook; Dale R. Gardner; James A. Pfister; Clinton A. Stonecipher; Joseph G. Robins; Jack A. Morgan (Journal of Chemical Ecology, 2017)

Spatial reconstruction of Scottish summer temperatures from tree rings - Miloš Rydval; Björn E. Gunnarson; Neil J. Loader; Edward R. Cook; Daniel L. Druckenbrod; Rob Wilson (International Journal of Climatology, 2017)
A detailed understanding of past temporal patterns and spatial expression of temperature variations is important to place recent anthropogenic climate change into a longer term context. In order to fill the current gap in our understanding of northwest European temperature variability, point‐by‐point principal component regression was used to reconstruct a spatial field of 0.5° temperature grids across Scotland. A sequence of reconstructions utilizing several combinations of detrending and disturbance correction procedures, and a selection of tree‐ring parameters [including ring width ( RW ), maximum latewood density ( MXD ) and blue intensity ( BI )] was used in an evaluation of reconstruction skill. The high resolution of the reconstructed field serves also as a diagnostic tool to spatially assess the temperature reconstruction potential of local chronologies. Best reconstruction results, reaching calibration r 2 = 65.8% and verification r 2 = 63.7% in central Scotland over the 1901–1976 period, were achieved using disturbance‐corrected and signal‐free detrended RW chronologies merged with BI data after low‐pass (high‐pass) filtering the RW ( BI ) chronologies. Calibration and verification r 2 > 50% was attained for central, north and east Scotland, >40% in west and northwest, and >30% in southern Scotland with verification of nearly all grids showing some reconstruction skill. However, the full calibration potential of reconstructions outside central Scotland was reduced either due to residual disturbance trends undetected by the disturbance correction procedure or due to other climatic or non‐climatic factors which may have adversely affected the strength of the climate signal.

Assessing the genetic architecture of epithelial ovarian cancer histological subtypes - Gabriel Cuellar-Partida; Yi Lu; Suzanne C. Dixon; Peter A. Fasching; Alexander Hein; Stefanie Burghaus; Matthias W. Beckmann; Diether Lambrechts; Els Van Nieuwenhuysen; Ignace Vergote; Adriaan Vanderstichele; Jennifer Anne Doherty; et al. (Human Genetics, 2016)

Selection of yeast strains for bioethanol production from UK seaweeds - Emily T. Kostas; Daniel A. White; Chenyu Du; David J. Cook (Journal of Applied Phycology, 2016)
Macroalgae (seaweeds) are a promising feedstock for the production of third generation bioethanol, since they have high carbohydrate contents, contain little or no lignin and are available in abundance. However, seaweeds typically contain a more diverse array of monomeric sugars than are commonly present in feedstocks derived from lignocellulosic material which are currently used for bioethanol production. Hence, identification of a suitable fermentative microorganism that can utilise the principal sugars released from the hydrolysis of macroalgae remains a major objective. The present study used a phenotypic microarray technique to screen 24 different yeast strains for their ability to metabolise individual monosaccharides commonly found in seaweeds, as well as hydrolysates following an acid pre-treatment of five native UK seaweed species ( Laminaria digitata , Fucus serratus , Chondrus crispus , Palmaria palmata and Ulva lactuca ). Five strains of yeast (three Saccharomyces spp, one Pichia sp and one Candida sp) were selected and subsequently evaluated for bioethanol production during fermentation of the hydrolysates. Four out of the five selected strains converted these monomeric sugars into bioethanol, with the highest ethanol yield (13 g L −1 ) resulting from a fermentation using C. crispus hydrolysate with Saccharomyces cerevisiae YPS128. This study demonstrated the novel application of a phenotypic microarray technique to screen for yeast capable of metabolising sugars present in seaweed hydrolysates; however, metabolic activity did not always imply fermentative production of ethanol.

Systems genetics of intravenous cocaine self-administration in the BXD recombinant inbred mouse panel - Price E. Dickson; Mellessa M. Miller; Michele A. Calton; Jason A. Bubier; Melloni N. Cook; Daniel Goldowitz; Elissa J. Chesler; Guy Mittleman (Psychopharmacology, 2016)

Quantifying the effects of light intensity on bioproduction and maintenance energy during photosynthetic growth of Rhodobacter sphaeroides - Saheed Imam; Colin M. Fitzgerald; Emily M. Cook; Timothy J. Donohue; Daniel R. Noguera (Photosynthesis Research, 2015)

Genome-wide association study of subtype-specific epithelial ovarian cancer risk alleles using pooled DNA - Madalene A. Earp; Linda E. Kelemen; Anthony M. Magliocco; Kenneth D. Swenerton; Georgia Chenevix-Trench; Yi Lu; Alexander Hein; Arif B. Ekici; Matthias W. Beckmann; Peter A. Fasching; Diether Lambrechts; Evelyn Despierre; et al. (Human Genetics, 2014)

Efficiency and robustness of ant colony transportation networks - Zoe Cook; Daniel W. Franks; Elva J. H. Robinson (Behavioral Ecology and Sociobiology, 2014)

GidA Expression in Salmonella is Modulated Under Certain Environmental Conditions - Jaclyn M. Rehl; Daniel C. Shippy; Nicholas M. Eakley; Megan D. Brevik; Jordan M. Sand; Mark E. Cook; Amin A. Fadl (Current Microbiology, 2013)

A novel approach of homozygous haplotype sharing identifies candidate genes in autism spectrum disorder - Jillian P. Casey; Tiago Magalhaes; Judith M. Conroy; Regina Regan; Naisha Shah; Richard Anney; Denis C. Shields; Brett S. Abrahams; Joana Almeida; Elena Bacchelli; Anthony J. Bailey; Gillian Baird; et al. (Human Genetics, 2012)

Reconciling estimates of the contemporary North American carbon balance among terrestrial biosphere models, atmospheric inversions, and a new approach for estimating net ecosystem exchange from inventory‐based data - Daniel J. Hayes; David P. Turner; Graham Stinson; A. David McGuire; Yaxing Wei; Tristram O. West; Linda S. Heath; Bernardus de Jong; Brian G. McConkey; Richard A. Birdsey; Werner A. Kurz; Andrew R. Jacobson; et al. (Global Change Biology, 2012)
We develop an approach for estimating net ecosystem exchange ( NEE ) using inventory‐based information over North America ( NA ) for a recent 7‐year period (ca. 2000–2006). The approach notably retains information on the spatial distribution of NEE , or the vertical exchange between land and atmosphere of all non‐fossil fuel sources and sinks of CO 2 , while accounting for lateral transfers of forest and crop products as well as their eventual emissions. The total NEE estimate of a −327 ± 252 TgC yr −1 sink for NA was driven primarily by CO 2 uptake in the Forest Lands sector (−248 TgC yr −1 ), largely in the Northwest and Southeast regions of the US, and in the Crop Lands sector (−297 TgC yr −1 ), predominantly in the Midwest US states. These sinks are counteracted by the carbon source estimated for the Other Lands sector (+218 TgC yr −1 ), where much of the forest and crop products are assumed to be returned to the atmosphere (through livestock and human consumption). The ecosystems of Mexico are estimated to be a small net source (+18 TgC yr −1 ) due to land use change between 1993 and 2002. We compare these inventory‐based estimates with results from a suite of terrestrial biosphere and atmospheric inversion models, where the mean continental‐scale NEE estimate for each ensemble is −511 TgC yr −1 and −931 TgC yr −1 , respectively. In the modeling approaches, all sectors, including Other Lands, were generally estimated to be a carbon sink, driven in part by assumed CO 2 fertilization and/or lack of consideration of carbon sources from disturbances and product emissions. Additional fluxes not measured by the inventories, although highly uncertain, could add an additional −239 TgC yr −1 to the inventory‐based NA sink estimate, thus suggesting some convergence with the modeling approaches.

Influence of Phenological Stage on Swainsonine and Endophyte Concentrations in Oxytropis sericea - Daniel Cook; Lei Shi; Dale R. Gardner; James A. Pfister; Daniel Grum; Kevin D. Welch; Michael H. Ralphs (Journal of Chemical Ecology, 2012)

Tobacco withdrawal components and their relations with cessation success - Megan E. Piper; Tanya R. Schlam; Jessica W. Cook; Megan A. Sheffer; Stevens S. Smith; Wei-Yin Loh; Daniel M. Bolt; Su-Young Kim; Jesse T. Kaye; Kathryn R. Hefner; Timothy B. Baker (Psychopharmacology, 2011)

Tolerance of nonindigenous cichlid fishes (Cichlasoma urophthalmus, Hemichromis letourneuxi) to low temperature: laboratory and field experiments in south Florida - Pamela J. Schofield; William F. Loftus; Robert M. Kobza; Mark I. Cook; Daniel H. Slone (Biological Invasions, 2010)

Swainsoninine Concentrations and Endophyte Amounts of Undifilum oxytropis in Different Plant Parts of Oxytropis sericea - Daniel Cook; Dale R. Gardner; Michael H. Ralphs; James A. Pfister; Kevin D. Welch; Benedict T. Green (Journal of Chemical Ecology, 2009)

The Biogeographical Distribution of Duncecap Larkspur (Delphinium occidentale) Chemotypes and Their Potential Toxicity - Daniel Cook; Dale R. Gardner; James A. Pfister; Kevin D. Welch; Benedict T. Green; Stephen T. Lee (Journal of Chemical Ecology, 2009)

Is (−)-Catechin a Novel Weapon of Spotted Knapweed (Centaurea stoebe)? - Stephen O. Duke; Amy C. Blair; Franck E. Dayan; Robert D. Johnson; Kumudini M. Meepagala; Daniel Cook; Joanna Bajsa (Journal of Chemical Ecology, 2009)

A cross‐taxa phenological dataset from Mohonk Lake, NY and its relationship to climate - Benjamin I. Cook; Edward R. Cook; Paul C. Huth; John E. Thompson; Anna Forster; Daniel Smiley (International Journal of Climatology, 2008)
We present a detailed analysis of a rare cross‐taxa native species phenology dataset (plant flowering, insect first sighting, and amphibian first sighting) from Mohonk Lake, NY. This dataset is highly unusual in North America for its longevity of record, consistency of methodology and location, diversity of species available, and availability of local daily meteorological data. For each phenology series, we examined the flowering and first sighting Julian calendar dates for the existence of temporal trends. Only one of the five animal species (katydid) showed any evidence for a significant trend in first sighting. In contrast, the plant species showed a rich mixture of temporal trends in flowering that could be divided into four classes: woody plant–no trend, woody plant–negative trend, herbaceous plant–negative trend, and herbaceous plant–positive trend. Many of the trends were found to be statistically significant and robust to the method of trend estimation. The data within each of the four plant classes were also pooled as anomalies to provide more complete temporal coverage for tests of trend robustness. The results were strongly consistent with the trends of the individual species within each class and highly significant statistically. We next correlated the flowering and first sighting dates against growing degree‐day (GDD) summations for each day of the year to measure the sensitivity of each species to this common form of climatic forcing on phenology. All species showed a significant sensitivity to GDD summations, with peak correlations falling on or near the varying median flowering or first sighting dates. These results were robust whether the GDD analyses were conducted over the complete set of observations for each species (beginning on or after 1928) or over a latter period with a more serially complete set of cross‐taxa observations (1970–2002). The GDD correlations indicate significant climate sensitivity in all species, but the different magnitudes of correlation and timing of maximum correlation imply that plant and animal responses to climate changes in the future will not be homogeneous for the tested species at Mohonk Lake. Copyright © 2007 Royal Meteorological Society

Tree-ring reconstructed megadroughts over North America since a.d. 1300 - David W. Stahle; Falko K. Fye; Edward R. Cook; R. Daniel Griffin (Climatic Change, 2007)

Agreement of diagnosis and its date for hematologic malignancies and solid tumors between medicare claims and cancer registry data - Soko Setoguchi; Daniel H. Solomon; Robert J. Glynn; E. Francis Cook; Raisa Levin; Sebastian Schneeweiss (Cancer Causes & Control, 2007)

Alkaloid Profiles, Concentration, and Pools in Velvet Lupine (Lupinus leucophyllus) Over the Growing Season - Stephen T. Lee; Michael H. Ralphs; Kip E. Panter; Daniel Cook; Dale R. Gardner (Journal of Chemical Ecology, 2007)

Congruent patterns of genetic variation in a burrowing freshwater crab revealed by allozymes and mt DNA sequence analysis - Savel R. Daniels; Barbara A. Stewart; Peter A. Cook (Hydrobiologia, 2002)

Stability in the historical pattern of genetic structure of Newfoundland cod (Gadus morhua) despite the catastrophic decline in population size from 1964 to 1994 - Daniel E. Ruzzante; Christopher T. Taggart; Roger W. Doyle; Doug Cook (Conservation Genetics, 2001)

Abstracts of presentations on plant protection issues at the fifth international Mango Symposium Abstracts of presentations on plant protection issues at the Xth international congress of Virology - J. E. Peña; M. Wysoki; Gajendra Singh; Nancy Boscán de M.; Freddy J. Godoy; A. Obligado; C. J. Rossetto; I. J. A. Ribeiro; P. B. Gallo; N. B. Soares; J. C. Sabino; A. L. M. Martins; et al. (Phytoparasitica, 1997)

Initial steps in the degradation of benzene sulfonic acid, 4-toluene sulfonic acids, and orthanilic acid in Alcaligenes sp. strain O-1 - Thomas Thurnheer; Daniel Zrrer; Otmar Hglinger; Thomas Leisinger; Alasdair M. Cook (Biodegradation, 1990)